Pengaruh Kreativitas Guru PAI dalam Mengajar Terhadap Minat Belajar Siswa SMP Negeri 2 Buluspesantren - 'Azizah, Farkhah; Faisal, Faisal (IAINU Kebumen, 2024)
This research aims to determine is there any influence of PAI teacher creativity in teaching on student’s interest in learning at SMP Negeri 2 Buluspesantren and how much influence teachers’ creativity in teaching has on students’ interest in learning at junior high school. The methode used is descriptive quantitative and this research includes survey research. The data collection teachniques used were questionnaire distribution, observation and documentation. Meanwhile, the data research technique used is simple linier regression.The results of this research show that there is an influence of teacher creativity on students’interest in learning, this is proven by a significance value of 0.00<0.05 probability value. And the magnetude of the influence namely15.58%. this is proven by KD = r2 (0.1558) × 100 so =15.58 / 100% = 15.58%. So the remaining 84.42% of clas VII students’interest in learning in PAI subjects at SMP Negeri 2 Buluspesantren is influenced by other factors not discussed in this research.